2017
DOI: 10.1016/j.ipej.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

First rib and venous anomalies – Anatomical challenges for transvenous implantation of cardiac electronic devices

Abstract: Atypical anatomy may be encountered unexpectedly and undiagnosed in clinical practice, and this is especially important during the performance of interventional procedures such as transvenous implantation of cardiac electronic devices. The body of the first rib can be absent. If this not noticed, pneumo-/haemothroax may be induced during subclavian vein puncture as the needle may enter the first intercostal space rather than the costo-clavicular angle. The cephalic vein may pursue a supraclavicular course, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Based on the classification, Kameda et al [13] suggested each frequency of subtypes as 0.4%, 1.2%, 0.4%, and 0.2%, respectively. They suggested single case report related with the variations [1,5,14,15,21,23,25,33,35] and we found some more case reports related with this variation: three for subtype 1A [2,8,12], three for subtype 1B [19,27], and one for subtype 2A [9]. The case 1 and 2 belong to subtype 1B and 1A, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…Based on the classification, Kameda et al [13] suggested each frequency of subtypes as 0.4%, 1.2%, 0.4%, and 0.2%, respectively. They suggested single case report related with the variations [1,5,14,15,21,23,25,33,35] and we found some more case reports related with this variation: three for subtype 1A [2,8,12], three for subtype 1B [19,27], and one for subtype 2A [9]. The case 1 and 2 belong to subtype 1B and 1A, respectively.…”
Section: Discussionsupporting
confidence: 54%
“…Venous anomalies could also be found in such cases. 1 An alternative approach in this situation may have been change to a subclavian access technique, which instead uses the medial clavicle and sternal notch as anatomical landmarks, to consider extending the incision laterally to identify the cephalic vein, or a right-sided implantation.…”
mentioning
confidence: 99%